Fiscal policies in agriculture and producer support estimates in Latin America and the Caribbean - Díaz-Bonilla, Eugenio; De Salvo, Carmine Paolo (Food and Agriculture Organization of the United Nations, 2019)
Fiscal policies have multiple effects on the economy and, therefore, on the agricultural sector and rural economies within it. This paper analyzes agricultural taxes and agricultural expenditures; it also looks into different forms of public policy support for agricultural producers and follows the Producer Support Estimates (PSE) methodology already applied to the Latin America and the Caribbean (LAC) region. This methodology combines fiscal support and other forms of support, such as those deriving from trade policies. Finally, this paper presents a summary of evaluation studies about different types of public expenditure for agriculture and draws some conclusions.